Pengaruh Tingkat Pendidikan Orang Tua dan Pola Asuh terhadap Hasil Belajar Matematika - Eli Marlina; Didik Tri Setiyoko; Laelia Nurpratiwiningsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of parents' education level and parenting pattern on learning outcomes of flat wake-up themes in fourth grade students of SD Negeri Kendaga. The method used is ex post facto with a quantitative approach. The data collection technique used is a questionnaire for the variable level of parents' education and the variable of parenting, while the learning outcomes variable uses a daily test score list on the flat wake theme of fourth grade students at SD Negeri Kendaga. This study was analyzed using SPSS software version 16 with a t-test on the level of parental education (X1) on learning outcomes (Y) the results of the sig value of 0.024 <0.05 with (X1) having an influence on (Y). T-test on the parenting style variable (X2) on learning outcomes (Y) with a sig value of 0.009 <0.05 thus (X2) has an influence on (Y). Then the F test of parents' education level (X1) and parenting (X2) on learning outcomes (Y) with Ftable of 3, 59 obtained Fcount of 9.727 thus (X1) and (X2) have an effect on (Y). coefficient of determination is 0.549 thus the variables in this study have an influence of 54.9%.